Bouveret’s Syndrome – Case Series with Therapeutic Implications - Kukiolka, Tobias; Borovicka, Jan; Baumeler, Stephan; Schiesser, Marc; Gubler, Christoph (Zeitschrift für Gastroenterologie, 2020)
Bouveret’s syndrome is a rare complication resulting from gallstone disease. Both surgical and endoscopical procedures are performed, with the disease to be seen as strictly interdisciplinary. There are no well-established recommendations for this condition. In this paper, we want to describe our experience from 6 cases in 3 Swiss hospitals from 2015 to 2017 with emphasis on the endoscopic technique of electrohydraulic lithotripsy followed by balloon dilatation and propose a treatment algorithm.
Keywords: Bouveret’s syndrome; gallstone ileus; electrohydraulic lithotripsy; balloon dilatation